A novel 4H-SiC lateral bipolar junction transistor structure with high voltage and high current gain - 邓永辉 谢刚 汪涛 盛况 (Chinese physics B, 2013)
In this paper, a novel structure of a 4H-SiC lateral bipolar junction transistor （LBJT） with a base tield plate and double RESURF in the drift region is presented. Collector-base junction depletion extension in the base region is restricted by the base field plate. Thin base as well as low base doping of the LBJT therefore can be achieved under the condition of avalanche breakdown. Simulation results show that thin base of 0.32 μm and base doping of 3 × 1017 cm 3 are obtained, and corresponding current gain is as high as 247 with avalanche breakdown voltage of 3309 V when the drift region length is 30 μm. Besides, an investigation of a 4H-SiC vertical BJT （VBJT） with comparable breakdown voltage （3357 V） shows that the minimum base width of 0.25 ~tm and base doping as high as 8 × 10^17 cm^-3 contribute to a maximum current gain of only 128.